2014
DOI: 10.1021/jo502563z
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diiodocalix[4]arene: Synthesis by Ullmann-Type Iodination of 1,3-Bistriflate Ester of Calix[4]arene, Conformational Analysis, and Transformation into 1,3-Dicarboxy-, Diformyl-, and Dialkylcalix[4]arenes

Abstract: A facile synthesis of 1,3-diiodocalix[4]arene 6 has been achieved by copper-catalyzed iodination of the 1,3-bistriflate ester 2a of p-tert-butylcalix[4]arene. After protection of the hydroxy groups with iodomethane, diiodide 6 is subjected to halogen–lithium exchange with butyllithium, followed by carbonation with CO2 or formylation with N-formylpiperidine and subsequent deprotection of the hydroxy groups to give novel dicarboxylic acid 11 or dialdehyde 16 in practical yields. The iodo groups of diiodide 6 pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…From the extracted organic phase, back-extraction of Pd(II) and Pt(II) was easily performed. We expect that molecular design based on our synthetic protocol for the direct replacement of the hydroxy groups of calix [4]arenes with other coordinating groups [35][36][37][38] will enable the development of selective extractants for various metals including other PGMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the extracted organic phase, back-extraction of Pd(II) and Pt(II) was easily performed. We expect that molecular design based on our synthetic protocol for the direct replacement of the hydroxy groups of calix [4]arenes with other coordinating groups [35][36][37][38] will enable the development of selective extractants for various metals including other PGMs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to the best of our knowledge, there is no report on the selective extraction of other PGMs with calix-based extractants in the presence of Pd. We previously reported the synthesis of hybrid-type calixarenes, [35][36][37][38] in which two distal phenolic hydroxy groups of calix [4]arenes are directly replaced with other coordinating groups. We applied the novel calixarenes as metal extractants and succeeded in the selective extraction of Yb(III) from lanthanoid ions 39 and Zr(IV) over Hf(IV) 40 using calix [4]arenediphosphonic acid, and that of Pd(II) from PGMs using calix [4]arenedicarboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Melting points were taken with a micro melting point apparatus and are uncorrected. 1 H and 13 C NMR spectra were measured with tetramethylsilane as an internal standard and CDCl 3 as a solvent unless otherwise noted. Silica gel (63−200 μm) was used for column chromatography and TLC.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Although phosphorus atomic groups have been directly introduced into the wide rims of calix[4]­arenes, there have been few reports of success in such chelate formation . For narrow-rim derivatives, because there has been no versatile synthetic method to displace the hydroxy groups with other functions by cleaving the aryl–oxygen bonds, phosphorus atomic groups had to be introduced on the phenoxy oxygens either directly or indirectly through linkers, which locates the coordinating groups apart from the calix skeleton, thereby making it difficult to form a tight chelate. Recently, we found that Ullmann-type reactions are applicable to 1,3-bis­(triflate ester) 2 , which provided easy access to diamine 3 , diphosphonic acid 4 , and diiodide 5 . In this study, we prepared diphosphine 7 via Ullmann-type phosphinoylation (compound 6 ) and investigated its complexation ability toward palladium­(II) ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation